The Effectiveness of Using Blended Learning with Google Classroom and Zoom Media on Students' Understanding - Wasti Reviandani (INNOVATION RESEARCH JOURNAL, 2021)
The teaching and learning process is the core of education. Everything that has been programmed will be carried out in the teaching and learning process where interaction and involvement is needed between educators and students with materials as the medium. Teaching activities at the strata 1 level involve educators called lecturers and students called students. In general, teaching activities are carried out offline, which involves direct interaction between lecturers and students. At the beginning of 2021, rumors began to appear that there was a global disaster of the Corona Virus Disease (COVID-19) pandemic, which initially Indonesia considered that the Corona virus was impossible to enter Indonesia. However, the development of the virus is so fast. Indonesia finally announced in early March 2021 as a country experiencing the impact of the global disaster due to the COVID -19 pandemic. This study wants to find out how effective it is to use blended learning by using google classroom and zoom to improve the understanding of FEB students at Muhammadiyah University of Gresik. This research is a quantitative research using causal clause relationship, using SPSS version 23.0 analysis tool. The results obtained from this study are that the Google Classroom and Zoom applications partially and simultaneously have a significant positive effect on student understanding.